Leonurine Promotes the Osteoblast Differentiation of Rat BMSCs by Activation of Autophagy via the PI3K/Akt/mTOR Pathway - Zhao, Bingkun; Peng, Qian; Poon, Enoch Hin Lok; Chen, Fubo; Zhou, Rong; Shang, Guangwei; Wang, Dan; Xu, Yuanzhi; Wang, Raorao; Qi, Shengcai (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Leonurine, a major bioactive component from Herba leonuri, has been shown to exhibit anti-inflammatory and antioxidant effects. The aim of this study was to investigate the effect of leonurine on bone marrow-derived mesenchymal stem cells （BMSCs） as a therapeutic approach for treating osteoporosis. Materials and Methods: Rat bone marrow-derived mesenchymal stem cells (rBMSCs) were isolated from 4-week-old Sprague-Dawley rats. The cytocompatibility of leonurine on rBMSCs was tested via CCK-8 assays and flow cytometric analyses. The effects of leonurine on rBMSC osteogenic differentiation were analysed via ALP staining, Alizarin red staining, quantitative real-time polymerase chain reaction (qRT-PCR), and western blotting. Additionally, autophagy-related markers were examined via qRT-PCR and western blot analyses of rBMSCs during osteogenic differentiation with leonurine and with or without 3-methyladenine (3-MA) as an autophagic inhibitor. Finally, the PI3K/Akt/mTOR signalling pathway was evaluated during rBMSC osteogenesis. Results: Leonurine at 2 to 100 μM promoted the proliferation of rBMSCs. ALP and Alizarin red staining results showed that 10 μM leonurine promoted rBMSC osteoblastic differentiation, which was consistent with the qRT-PCR and western blot results. Compared with those of the control group, the mRNA and protein levels of Atg5, Atg7 and LC3 were upregulated in the rBMSCs upon leonurine treatment. Furthermore, leonurine rescued rBMSC autophagy after inhibition by 3-MA. Additionally, the PI3K/AKT/mTOR pathway was activated in rBMSCs upon leonurine treatment. Conclusions: Leonurine promotes the osteoblast differentiation of rBMSCs by activating autophagy, which depends on the PI3K/Akt/mTOR pathway. Our results suggest that leonurine may be a potential treatment for osteoporosis.